Constant speed control of a permanent-magnet synchronous motor using a reverse matrix converter under variable generator input conditions - Bak, Yeongsu; Lee, Kyo Beum (IEEE Journal of Emerging and Selected Topics in Power Electronics, 2018)
This paper proposes a control strategy for a permanent-magnet synchronous motor (PMSM) fed by an indirect matrix converter (IMC) operating in boost mode. In order to increase the voltage transfer ratio of the IMC, a structure of the IMC having the inverse direction of power flow is adopted, which is called a reverse matrix converter (RMC). This structure operates in boost mode without additional elements or circuits. In this paper, although a generator having variable conditions is used for the input stage of the RMC system, the PMSM of the output stage can be controlled to a constant speed through the proposed control strategy. The validity of the proposed control strategy is demonstrated by simulation and experimental results.
Keywords: Boost mode; Carrier based modulations; Indirect matrix converter; Permanent magnet motor; Permanent Magnet Synchronous Motor; Boost mode; Carrier-based modulation; Indirect matrix converter (IMC); Permanent-magnet synchronous motor (PMSM); Reverse matrix converter (RMC)